High Potential of Liquid Smoke from Coconut Shell (Cocos nucifera) for Biological Control of Rice Bug (Leptocorisa oratorius Fabricius) - Gama, Zulfaidah Penata; Purnama, Rizky Mulyo Adi; Melani, Dewi (Journal of Tropical Life Science, 2021)
Rice bug (Leptocorisa oracorius F) is one of the most dangerous pests for paddy commodities (Oryza sativa) in the world. The use of liquid smoke was popular among local farmers to control rice bug. A coconut shell is the main source for making liquid smoke. This research aims to analyse rice bugs' mortality and antifeedant activity when dipped with coconut shell liquid smoke. The liquid smoke's effectiveness was measured by dipping paddy (5 grams in weight) that is previously soaked with coconut shell liquid for 20 seconds. The liquid smoke was prepared in various concentrations, ranging from 0% as a control; 0.50%; 0.75%; 1%; 1.25% and 1,50%. Observations were made at 24, 48, 72, 96, 120, 144 and 168 hours. Data analysis was performed by one-way ANOVA test, using SPSS program followed by a 0.05 Tukey test to determine the significance of the rice bug pest mortality. The study resulted that the mortality values from low concentrations to high concentrations were 40%, 46.67%, 60%, 70%, and 80% over seven days. The antifeedant percentage of liquid smoke increased from low concentrations to high concentrations respectively were 10.14%, 15.15%, 31.03%, 46.15%, and 68.88% during seven days. The concentration of liquid smoke that has the highest mortality was 1.50%. In conclusion, 1.50% of liquid smoke showed the highest percentage of mortality and antifeedant activity with 80% and 68.88%, respectively. In the future, it is hoped to develop this model for commercial consumption and reduce reliance on chemicals to control rice bugs. The use of pesticides can do more harm than good, especially to the environmental system.